Pengembangan Media KONEKSI Berbasis Website Genially pada Pembelajaran IPAS Kelas V SDN Genilangit 1 - Rendra Ari Wijaya; Endang Sri Maruti; Sesaria Prima Yudhaningtyas (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The aim of this study was to develop the ‘KONEKSI’ learning media based on the Genially website, for grade fifth IPAS lessons at Genilangit 1 elementary school. The background to this study was the need for interactive and engaging learning resources, particularly for the science subject. Observations and interviews at Genilangit 1 elementary school revealed that IPAS lessons remained teacher-centred and relied mainly on textbooks and worksheets, leaving pupils passive and finding it difficult to grasp abstract concepts such as harmony in the ecosystem. These conditions indicated the need for an interactive and contextual medium capable of supporting the topic more effectively. Analysis, design, development, implementation and evaluation are the five stages of the ADDIE R&D model. The Genially website was used to create interactive learning resources comprising learning materials, videos and interactive quizzes. Following validation, the subject matter expert, language expert and media expert scored 97.33% (Highly Acceptable), 85.33% (Highly Acceptable) and 89.33% respectively. The product was trialled on 22 student grade fifth ; both trials achieved the ‘Highly Suitable’ category, with an average questionnaire response rate of 95.63% and a 100% response rate from teachers. The research findings indicate that the KONEKSI teaching aid, based on the Genially website, can be effectively utilised in the IPAS learning process for grade fifth. The KONEKSI teaching aid, based on the Genially website, facilitates the delivery of material by teachers during the learning process and stimulates pupils’ interest in learning. It is hoped that this teaching aid can serve as a relevant alternative learning method in line with technological advancements.